Genome-wide analysis of the synonymous codon usage patterns in apple - Ning LI; Mei-hong SUN; Ze-sheng JIANG; Huai-rui SHU; Shi-zhong ZHANG (Journal of Integrative Agriculture, 2016)
Apple (Malus×domestica) has been proposed as an important woody plant and the major cultivated fruit trees in temperate regions. Apple whole genome sequencing has been completed, which provided an excellent opportunity for genome-wide analysis of the synonymous codon usage patterns. In this study, a multivariate bioinformatics analysis was performed to reveal the characteristics of synonymous codon usage and the main factors affecting codon bias in apple. The neutrality, correspondence, and correlation analyses were performed by CodonW and SPSS (Statistical Product and Service Solutions) programs, indicating that the apple genome codon usage patterns were affected by mutational pressure and selective constraint. Meanwhile, coding sequence length and the hydrophobicity of proteins could also influence the codon usage patterns. In short, codon usage pattern analysis and determination of optimal codons has laid an important theoretical basis for genetic engineering, gene prediction and molecular evolution studies in apple.